Cooperation between two strains of Enterobacter and Klebsiella in the simultaneous nitrogen removal and phosphate accumulation processes. (November 2019) - Zhang, Yuxiao; Xu, Zixiao; Li, Jingxin; Liu, Deli; Yuan, Yongze; Chen, Zhengjun; Wang, Gejiao
Highlights: Co-cultured bacteria could remove nitrogen and phosphate. High removal was achieved by inoculation with the co-strains in wastewater. The co-strains had a continuous removal effect in the batch reaction. The napA2, narG and ppk genes in the co-cultures were upregulated. In the co-cultured conditions, high levels of ATP and NADH were accumulated. Abstract: Two strains, Enterobacter sp. Z1 and Klebsiella sp. Z2, were exhibited great capacities for heterotrophic nitrification-aerobic denitrification (HNAD) and intracellular phosphate accumulation. Strikingly, the co-cultured strains enhanced the removal efficiency of total nitrogen and phosphate, with removal efficiencies of ammonia, nitrate, nitrite and soluble phosphate of 99.64%, 99.85%, 96.94% and 66.7% respectively. Furthermore, high removal efficiencies from wastewaters with high concentrations of ammonia (over 1000 mg/L) were achieved by inoculation with the co-strains, which left residual ammonia of less than 1 mg/L within 10 h. To elucidate the mechanism of HNAD in co-strains, quantitative PCR was carried out to examine the expression levels of hydroxylamine oxidase (Hao), nitrate reductase (NapA and NarG), nitrite reductase (NirS) and polyphosphate kinase (Ppk), and the results showed that the napA2, narG and ppk genes in the strains were significantly upregulated under the co-cultured conditions and provided an explanation for the nitrogen and phosphate removal.